Acoustic emission characteristics and damage evolution of coal gasification slag-based geopolymer cement grouting materials - Wenyue QI; Yanli HUANG; Qingxin ZHAO; Xiaotian LIU; Yongji HAN (Meitan kexue jishu, 2025)
The accumulation of low-quality coal-based solid waste presentes a significant risk to ecological and environmental safety. The concealment of the efficacy and destruction process of coal-based solid waste grout is a concern. The composite coal gangue sand with a tailored gradation was employed as the fine aggregate, and a geopolymer-based coal gasification slag formulation, experimentally optimized, was utilized to formulate the grouting material. Subsequent to this, the flowability and mechanical integrity of the grouting material were evaluated. Concurrently, acoustic emission non-destructive testing methodology was employed to monitor the acoustic emission characteristics exhibited by the grouting mass throughout its destructuration phase. The findings of the study suggested that the activation effect of the grouting materials reached its peak when the coal gasification coarse slag was finely ground for a duration of 70 minutes. Furthermore, an increase in the mass concentration and a decrease in the sand-to-cement ratio were observed to correlate positively with the compressive strength of the cementitious body, while negatively impacting its fluidity. Among the various factors examined, the mass concentration emerged as the pivotal parameter influencing the compressive strength. The ringing count and energy values, b-value and amplitude feature, and RA–AF analysis of the acoustic emission data revealed that the damage progression in the specimens can be categorized into four distinct stages: pore compaction, crack initiation, crack propagation, and post-peak failure. During the stages of crack initiation and crack propagation, there is a marked increase in the ringing count and cumulative values, and energy values and cumulative values. However, in the post-peak failure stage, these metrics generally exhibit a trend towards stabilization. Furthermore, the b-value analysis elucidates the distributional properties of the internal crack sizes within the material, where the b-value presents a fluctuating trend during the stages of crack initiation and propagation, characterized by significant fluctuations and abrupt changes in values. Subsequent to the peak failure stage, the b-value tends towards a state of equilibrium. The median amplitude, as well as the count of medium-high amplitude acoustic emission events exceeding 1.5 interquartile range, demonstrates a trend of initial incrementation followed by stabilization, reaching a maximum during the stage of crack propagation. The specimens primarily exhibited tensile damage failure, with shear damage being secondary in nature. The findings of this research provides theoretical underpinnings for the monitoring of damage progression and failure mechanisms in grouting materials.